On the Fourier-Transformed Boltzmann Equation with Brownian Motion - Yong-Kum Cho; Eunsil Kim (Abstract and Applied Analysis)
We establish a global existence theorem, and uniqueness and stability of solutions of the Cauchy problem for the Fourier-transformed Fokker-Planck-Boltzmann equation with singular Maxwellian kernel, which may be viewed as a kinetic model for the stochastic time-evolution of characteristic functions governed by Brownian motion and collision dynamics.